Cat problems - John, Jory; Smith, Lane (New York : Random House Studio, 2021)
A pampered house cat complains about the daily struggles he faces.
K-3.
AD500L
Keywords: Cats -- Juvenile fiction; Humorous stories; Cats -- Fiction; Humorous stories; Humorous fiction; Animal fiction